The Relationship between Self-Confidence and Teeth Stain Caused by Coffee Consumption and Smoking on Dentistry Student of Universitas Prima Indonesia - Nababan, Idamawati; Molek; Sharon Altin Taqwani (HM Publisher, 2024)
Teeth stains occur due to the presence of polyphenol compounds that provide color to beverages, together with inadequate oral hygiene that leads to the formation of calculus and plaque. In addition to coffee, cigarettes are also a contributing factor to the formation of stains. This study was aimed to determine the relationship between self-confidence in dentistry students of Universitas Prima Indonesia and teeth staining from smoking and coffee use. This study is a cross-sectional analytical-observational investigation. This study utilizes original data acquired from research participants. This study involved a cohort of 53 research subjects. The data analysis was conducted using the univariate and bivariate methods in SPSS version 25. The Kruskal-Wallis test revealed a statistically significant disparity in the average tooth discoloration across individuals with varying levels of self-confidence (p=0.0001; p≤0.05). The findings of this study indicate a correlation between students' self-assurance and alterations in tooth color resulting from smoking and coffee consumption.